Profit or Planet? : Impact of Production and Environmental Costs on Sales - Ivada Zanetha Darmaputri; Valentine Siagian (Yayasan Ilomata, 2023)
Lately, environmental problems such as pollution, poorly managed waste, and even depleting green land, have become issues that require companies to take action. But on the other hand, companies need well-allocated production costs, which of course have the aim of increasing company profits. That’s why, the purpose of this research is to analyze The Effects of Production Costs and Environmental Costs on Sales for primary and chemical industry firms with ISO 14001 certification that are traded on the Indonesia Stock Exchange. Specifically, SPSS version 27 is utilized for conducting multiple regression analyses as part of a quantitatively descriptive methodology. Annual and sustainability reports for 5 years from 2017 to 2021 out of 8 companies that have gone through a purposive sampling process are used as research samples. Based on the multiple regression analysis that has been carried out, the results show that partially, production costs have a significant effect on sales, and environmental costs have no significant effect on sales. Meanwhile, simultaneously both production costs and environmental costs have a significant effect on sales. Meaning that production costs and environmental costs are interconnected with each other, so when sales continue to increase, production costs and environmental costs will also increase.